Continence, quality of life and depression following surgical repair of obstetric vesicovaginal fistula: a cohort study. (27th December 2018) - Kopp, DM; Tang, JH; Bengtson, AM; Chi, BH; Chipungu, E; Moyo, M; Wilkinson, J
Abstract : Objective: We evaluated residual incontinence, depression, and quality of life among Malawian women who had undergone vesicovaginal fistula (VVF) repair 12 or more months previously. Design: Prospective cohort study. Setting: Fistula Care Centre in Lilongwe, Malawi. Population: Women who had undergone VVF repair in Lilongwe, Malawi at least 12 months prior to enrolment. Methods: Self‐report of urinary leakage was used to evaluate for residual urinary incontinence; depression was evaluated with the Patient Health Questionnaire‐9; quality of life was evaluated with the King's Health Questionnaire. Main outcome measures: Prevalence and predictors of residual incontinence, quality of life scores, and prevalence of depression and suicidal ideation. Results: Fifty‐six women (19.3%) reported residual urinary incontinence. In multivariable analyses, predictors of residual urinary incontinence included: pre‐operative Goh type 3 [adjusted risk ratio (aRR) 2.82; 95% confidence interval (CI) 1.61–5.27) or Goh type 4 1.08–2.78), positive postoperative cough stress test (aRR = 2.42; 95% CI 1.24–4.71) and the positive 1‐hour postoperative pad test (aRR = 2.20; 95% CI 1.08–4.48). Women with Goh types 3 and 4 VVF reported lower quality of life scores. Depressive symptoms were reported in 3.5% of women; all reported residual urinary incontinence. Conclusions: While the majority of women reported improved outcomes in the years following surgical VVF repair, those with residual urinary incontinence had a poorer quality of life. Services are needed to identify and treat this at‐risk group. Tweetable abstract: Nearly one in five women reported residual urinary incontinence at follow up, 12 or months after vesicovaginal fistula repair. Abstract : Tweetable abstract Nearly one in five women reported residual urinary incontinence at follow up, 12 or months after vesicovaginal fistula repair. This article includes Author Insights from 22 August 2019, a video abstract available at https://vimeo.com/rcog/authorinsights15546